Proceso de atención de enfermería en paciente con úlceras de pie diabético: un estudio de caso - Rivadeneira Sarango , Angie Liseth (2024)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia, which typically arises from an unhealthy lifestyle. This condition poses a significant challenge in the healthcare field due to its substantial impact on patients' quality of life. The present study aimed to implement a personalized nursing care process for patients with diabetes, utilizing Marjory Gordon's model to conduct a comprehensive assessment through functional patterns. This approach allowed for addressing not only the clinical manifestations of the disease but also identifying emotional and social needs that affect the well-being of the patient and their family. Through data collection, which included a thorough review of the medical history and nursing assessment, alterations in self-care and nutritional patterns were identified, leading to nursing diagnoses such as "imbalanced nutrition: less than body requirements" and "risk of infection." In response to these findings, interventions were developed that included education on self-care, promotion of hygiene practices, and glycemic control. As a result of the implemented interventions, a significant improvement in the clinical stability of the patient was observed, evidenced by a reduced risk of infections, better glucose control, and a noticeable improvement in the patient's overall health status. This underscores the importance of comprehensive care centered on the patient and their family.